Economic Security in Conditions of Uncertainty - ORLOVA, Anna V.; LYSHCHIKOVA, Julia V.; NIKULINA, Yevgenia V.; ANOKHIN, Yevgeny I. (Journal of Environmental Management and Tourism; Vol 7 No 3 (2016): JEMT Volume VII Issue 3(15) Fall 2016, 2016)
The article examines the prospects of economic security at the federal level. Ensuring economic security and counter internal and external threats to the economic security acts as one of the fundamental tasks of the state at the present stage. Economic security as a separate category is not limited to human, society and the state, but also on businesses throughout the economic system. The article deals with the basic elements of the mechanism of economic security, as well as features to ensure the economic security of Russia in modern conditions of uncertainty.
Keywords: economic security, economic security mechanism, conditions of uncertainty